Effects of maize and legume intercropping system on soil nitrogen dynamics and crop growth - Mmotong, Mmabopele Mokgethoa (My University, 2024)
Nitrogen is an essential mineral nutrient that can hinder crop production if not managed properly. Improved agricultural management practices such as cover cropping, crop rotations or intercropping influence nitrogen availability and supply. Hence this study was aimed at investigating how intercropping cereal with legume influences (i) soil nitrogen dynamics and (ii) selected growth and yield parameters. A field experiment was carried out at the University of Limpopo experimental farm (Syferkuil) integrating maize (Zea mays) with chickpea (Cicer arietinum) and mungbean (Vigna radiata) under two different moisture regimes (irrigated and rainfed). The experimental site was a split plot design replicated three times. The treatments were as follows: Sole maize- SM, Sole chickpea- SC, Sole mungbean- SMB, Maize/chickpea intercropping- MC, Maize/mungbean intercropping– MMB under rainfed and irrigated moisture regimes. Soil fertility variables i.e., bulk density, aggregate stability, pH, phosphorus and organic carbon; and nitrogen fractions: biological nitrogen fixation (BNF), mineralisation, uptake, residual and leaching were measured using standard procedures. Data analyses was done using the GenStat 20th Edition software. The study showed insignificant interaction effect between cropping system and irrigation regime did not have a significant effect on soil conditions bulk density, aggregate stability, pH, organic carbon (p>0.05). Nitrogen mineralisation was higher in the intercrops in comparison to the sole grown crops. Biological nitrogen fixation (BNF) was higher in the irrigated plot compared to the rainfed plot. Chickpea generally fixed a greater amount of nitrogen compared to mungbean. Chickpea showed greater nitrogen fixation in the intercropped stand while mungbean had a higher BNF in the sole stand. The uptake of nitrogen was greater in the irrigated compared to the rainfed plot. Sole maize had the highest nitrogen uptake, followed by the intercropped stands and then the sole legume stands. Residual nitrogen was greater in the rainfed plot compared to the irrigated plot. Intercropping both legume crops resulted in higher residual nitrogen compared to the sole stands. Mineral nitrogen leached beyond the active root zone was greater in the irrigated plot. The intercropped stands recorded lower mineral nitrogen leached in comparison to the sole stands. Data collected to observe growth and yield parameters were chlorophyll content, leaf area plant height and plant biomass. The results depicted a positive response to intercropping through the chlorophyll content and leaf area. Plant biomass was higher in in the sole stands for all associated crops. In conclusion, cereal/legume intercropping can be a sustainable approach to maximizing nitrogen use efficiency while minimizing potential losses.
Thesis (M.Sc. (Soil Science)) -- University of Limpopo, 2024
Keywords: Intercropping; Legumes; Soil fertility; Nitrogen dynamics; Water regime; Crop growth; Legumes; Intercropping; Soil fertility; Corn; Crops -- Growth